The impact of primary health care on AIDS incidence and mortality: A cohort study of 3.4 million Brazilians. - Priscila F P S Pinto; James Macinko; Andréa F Silva; Iracema Lua; Gabriela Jesus; Laio Magno; Carlos A S Teles Santos; Maria Yury Ichihara; Mauricio L Barreto; Corrina Moucheraud; Luis E Souza; Inês Dourado; et al. (PLoS Medicine)
Background Primary Health Care (PHC) is essential for effective, efficient, and more equitable health systems for all people, including those living with HIV/AIDS. This study evaluated the impact of the exposure to one of the largest community-based PHC programs in the world, the Brazilian Family Health Strategy (FHS), on AIDS incidence and mortality. Methods and findings A retrospective cohort study carried out in Brazil from January 1, 2007 to December 31, 2015. We conducted an impact evaluation using a cohort of 3,435,068 ≥13 years low-income individuals who were members of the 100 Million Brazilians Cohort, linked to AIDS diagnoses and deaths registries. We evaluated the impact of FHS on AIDS incidence and mortality and compared outcomes between residents of municipalities with low or no FHS coverage (unexposed) with those in municipalities with 100% FHS coverage (exposed). We used multivariable Poisson regressions adjusted for all relevant municipal and individual-level demographic, socioeconomic, and contextual variables, and weighted with inverse probability of treatment weighting (IPTW). We also estimated the FHS impact by sex and age and performed a wide range of sensitivity and triangulation analyses; 100% FHS coverage was associated with lower AIDS incidence (rate ratio [RR]: 0.76, 95% CI: 0.68 to 0.84) and mortality (RR: 0.68, 95%CI: 0.56 to 0.82). FHS impact was similar between men and women, but was larger in people aged ≥35 years old both for incidence (RR: 0.62, 95% CI: 0.53 to 0.72) and mortality (RR: 0.56, 95% CI: 0.43 to 0.72). The absence of important confounding variables (e.g., sexual behavior) is a key limitation of this study. Conclusions AIDS should be an avoidable outcome for most people living with HIV today and our study shows that FHS coverage could significantly reduce AIDS incidence and mortality among low-income populations in Brazil. Universal access to comprehensive healthcare through community-based PHC programs should be promoted to achieve the Sustainable Development Goals of ending AIDS by 2030.